Probing buried defects in zinc oxide nanoparticles using defect-mediated energy transfer - Beck, Lacey, author; Sambur, Justin, advisor; Prieto, Amy, committee member; Bartels, Randy, committee member (Colorado State University. Libraries, 2019)
Semiconductor nanocrystals are actively explored as light harvesting materials for solar energy conversion and optoelectronic applications such as solar cells and light emitting diodes. The underlying processes in such systems include charge carrier generation, recombination, and transport. Defects influence these underlying processes by introducing energy levels inside the semiconductor bandgap that trap charge carriers. Despite their critical importance, the real space distribution of defect sites in semiconductor nanocrystals is often unknown. Here we demonstrate an ensemble-level energy transfer measurement approach to study the radiative defect states in a size series of ZnO nanocrystals. In this approach, ZnO defects that have energy levels inside the band gap engage in energy transfer with surface adsorbed AlexaFluor dye molecule acceptors. By quantifying the defect-mediated energy transfer efficiency as a function of nanocrystal size and reaction time, we determined that the radiative defect sites in ZnO are located between the nanocrystal core and surface (i.e., near surface sites) and the distance between the defect sites and the surface increases as the nanocrystals grow larger. The all-optical energy transfer approach represents a non-destructive characterization method to determine the spatial distribution of defects in semiconductor nanocrystals. The defect distributions can be correlated with optoelectronic or photocatalytic properties to elucidate structure/function relationships in a wide range of applications that involve light-matter interactions.
Keywords: nanocrystals; energy transfer; zinc oxide